2010 Fourth International Conference on Sensor Technologies and Applications 2010
DOI: 10.1109/sensorcomm.2010.12
|View full text |Cite
|
Sign up to set email alerts
|

Latency and Packet Loss of an Interferred 802.15.4 Channel in an Industrial Environment

Abstract: Abstract-There is currently a rapid development of new types of wireless communication channels for industrial automation. This paper aims to provide some experimental data and theoretical justification on packet latency and packet loss for a wireless communication channel exposed to intentional radio interference. The intentional radio interference used in the experiments is an attempt to simulate possible future co-existence scenarios in a dense wireless communication environment at an industrial site. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Farrell et al [47] demonstrated that delays of 100-125 ms are not perceivable by the user and do not negatively influence the performance. The calculated packet loss rate was substantially smaller than those presented in [62][63][64], assuring stable Bluetooth transmission and transceiver communication. Furthermore, it allows for the possibility to increase the sampling rate of data communication without impacting the quality of the transmitted signal.…”
Section: Discussionmentioning
confidence: 71%
“…Farrell et al [47] demonstrated that delays of 100-125 ms are not perceivable by the user and do not negatively influence the performance. The calculated packet loss rate was substantially smaller than those presented in [62][63][64], assuring stable Bluetooth transmission and transceiver communication. Furthermore, it allows for the possibility to increase the sampling rate of data communication without impacting the quality of the transmitted signal.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, by avoiding device-to-cloud communication and instead using device-to-device communication, latency is reduced. The achieved latency depends on a number of factors [47], such as MAC layer performance, network size and topology, external electromagnetic noise. However, by using robust radio technologies and time-synchronous dutycycling, it is possible to deploy distributed applications with soft real-time performance.…”
Section: Discussionmentioning
confidence: 99%
“…Most industrial low rate wireless standards focus on the realtime communication based on the 802.15.4 physical (PHY) layer for a large-scale open-loop sensing and monitoring of the non-critical process automation [10], [60]. Some experimental results [61], [62], [63] show the applicability of the IEEE 802.15.4 PHY layer for harsh industrial environments. Although it is not originally designed for mission-critical applications, Bluetooth is also considered and reviewed as a candidate technology for WAIC systems.…”
Section: Candidate Wireless Solutions For Waicmentioning
confidence: 98%